2023
DOI: 10.1111/acfi.13089
|View full text |Cite
|
Sign up to set email alerts
|

Do women empower other women? Empirical evidence of the effect of female pervasiveness on firm risk‐taking

Abstract: This study examines the relationship between female pervasiveness within the entire company and firm‐risk taking. We exploit The UK Equality Act (2010), further enforced in 2017, which was made mandatory for firms operating in UK to disclose their gender pay gap. We use this measure to proxy female pervasiveness and we find it to be negatively associated with firm risk‐taking. These results are robust to several tests using female participation in each pay quartile and the difference in bonus payments between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Furthermore, through time series analysis, the authors find that an increase (decrease) in firm risk-taking is associated with female-to-male (male-to-female) CEO transitions. Perryman (2016) provides similar results by expanding this analysis to include female executives who are members of TMTs, while Ciappei et al (2023) found that female pervasiveness within the company to reduce firm risk-taking.…”
Section: Literature Review Of Studies On Womenmentioning
confidence: 72%
See 3 more Smart Citations
“…Furthermore, through time series analysis, the authors find that an increase (decrease) in firm risk-taking is associated with female-to-male (male-to-female) CEO transitions. Perryman (2016) provides similar results by expanding this analysis to include female executives who are members of TMTs, while Ciappei et al (2023) found that female pervasiveness within the company to reduce firm risk-taking.…”
Section: Literature Review Of Studies On Womenmentioning
confidence: 72%
“…More than two decades after the first law regulating gender diversity in corporate boards was introduced, concerns over its effectiveness and the need for legal mechanisms are being revisited. The gender pay gap regulation introduced in the UK in 2017 and European Union member states’ increasing focus on transparency and disclosure about women’s participation and their role in companies (Ciappei et al , 2023) represent confirmation of the growing public concern over the behavior of international companies. In this sense, the results of the study enable policymakers to make informed regulatory decisions and industry practitioners and civil society actors to understand key corporate outcomes (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations